Soft error study on junctionless silicon nanotube FET based 6T SRAM cell. (December 2020) - Durga, G; Srinivasan, R
Abstract: In this work, the response of Junctionless Silicon Nanotube FET (JL SiNT FET) to the heavy ion irradiation and the soft error performance of JL SiNT FET based SRAM circuit are investigated using 3D numerical simulations. The impact of single event transient (SET) is studied at different locations of junctionless SiNT with different incident angles to identify the sensitive location of the device. After SET analysis, JL SiNT FET based 6T SRAM cell is studied for single event upset (SEU). Heavy ion study of JL SiNT FET is compared with junction based SiNT FET. The simulation result shows that the threshold linear energy transfer (LETth ) of JL SiNT FET based SRAM is approximately three times lesser than the junction based SiNT FET SRAM.